Ts. Dr. Waheb creates Narrowband Internet of Things Enabled Flood Monitoring and Warning System - Hafizatulazlin, Abdul Aziz; Nur Hartini, Mohd Hatta (2021)
A lecturer from the Faculty of Electrical & Electronic Engineering Technology (FTKEE), Universiti Malaysia Pahang (UMP), Ts. Dr. Waheb Abdul Jabbar Shaif Abdullah, 42, created a system called Narrowband Internet of Things Enabled Flood Monitoring and Warning System (NB-IoT FMWS).